Globe penetration during loco-regional anesthesia: prevalence and review of cases - Alba Gómez-Benlloch; Maximiliano Olivera; Jeroni Nadal; Gemma Julio; Javier Elizalde (International Journal of Ophthalmology, 2022)
AIM: To describe prevalence and different clinical signs and management of cases with penetrating eye injuries during loco-regional anesthesia for ophthalmic surgery. METHODS: A retrospective review of clinical records was carried out, identifying cases of globe penetration secondary to peribulbar anesthesia injection during 5y activity in Centro de Oftalmología Barraquer. RESULTS: A total of 17 460 needle-based ocular anesthesia procedures were performed in our centre and 4 cases of globe penetration were recorded with an estimated prevalence of 0.024%. Globe penetrations were always detected in the first 24h after surgery. Vitreous haemorrhage was found in all the cases. Two eyes presented retinal detachment and two eyes choroidal detachment (CD). The initial surgical approach was performed within the first 48h. Silicone oil was used as tamponade in three eyes and the fourth case remained only with air. Detachments were solved successfully in all the cases. Functional results varied among cases, depending on ocular remarkable antecedent and globe penetration with or without retinal or CD. CONCLUSION: Prevalence of globe penetration during loco-regional anesthesia is low in our centre. Physicians should consider the possibility of globe penetration in eyes with postoperative atypical appearance after loco-regional anesthesia. Immediate B-scan ultrasonography is recommended in suspicious cases with a dense vitreous haemorrhage. An early vitrectomy surgery in conjunction with laser or cryotherapy at the penetration sites is essential for good anatomical and functional results.